Outcomes and toxicities of definitive radiotherapy and reirradiation using 3‐dimensional conformal or intensity‐modulated (pencil beam) proton therapy for patients with nasal cavity and paranasal sinus malignancies. Issue 9 (25th February 2020) - Fan, Ming; Kang, Jung Julie; Lee, Anna; Fan, Dan; Wang, Huili; Kitpanit, Sarin; Fox, Pamela; Sine, Kevin; Mah, Dennis; McBride, Sean M.; Tsai, Chiaojung Jillian; Riaz, Nadeem; et al.
Abstract : Background: Proton therapy (PT) improves outcomes in patients with nasal cavity (NC) and paranasal sinus (PNS) cancers. Herein, the authors have reported to their knowledge the largest series to date using intensity‐modulated proton therapy (IMPT) in the treatment of these patients. Methods: Between 2013 and 2018, a total of 86 consecutive patients (68 of whom were radiation‐naive and 18 of whom were reirradiated) received PT to median doses of 70 grays and 67 grays relative biological effectiveness, respectively. Approximately 53% received IMPT. Results: The median follow‐up was 23.4 months (range, 1.7‐69.3 months) for all patients and 28.1 months (range, 2.3‐69.3 months) for surviving patients. The 2‐year local control (LC), distant control, disease‐free survival, and overall survival rates were 83%, 84%, 74%, and 81%, respectively, for radiation‐naive patients and 77%, 80%, 54%, and 66%, respectively for reirradiated patients. Among radiation‐naive patients, when compared with 3‐dimensional conformal proton technique, IMPT significantly improved LC (91% vs 72%; P  < .01) and independently predicted LC (hazard ratio, 0.14; P  = .01). Sixteen radiation‐naive patients (24%) experienced acute grade 3 toxicities; 4 (6%) experienced late grade 3 toxicities (osteoradionecrosis, vision loss, soft‐tissue necrosis, and soft tissue fibrosis) (grading was performed according to the National Cancer Institute Common Terminology Criteria for Adverse Events [version 5.0]). Slightly inferior LC was noted for patients undergoing reirradiation with higher complications: 11% experienced late grade 3 toxicities (facial pain and brain necrosis). Patients treated with reirradiation had more grade 1 to 2 radionecrosis than radiation‐naive patients (brain: 33% vs 7% and osteoradionecrosis: 17% vs 3%). Conclusions: PT achieved remarkable LC for patients with nasal cavity and paranasal sinus cancers with lower grade 3 toxicities relative to historical reports. IMPT has the potential to improve the therapeutic ratio in these malignancies and is worthy of further investigation. Abstract : Patients who are radiotherapy‐naive and those who have been reirradiated achieve remarkable local control with proton therapy techniques in the management of nasal cavity and paranasal sinus cancers. To the authors' knowledge, the current study is the largest series to date to report outcomes and toxicity with intensity‐modulated proton therapy (IMPT) and has identified IMPT as an independent predictor of local control in the treatment of patients with these malignancies.